Artemsieverolactones A—H, Eight Guaiane‐Type Sesquiterpenoid Trimers from Artemisia sieversiana - Dong, Wei; Huang, Xiao‐Yan; Li, Tian‐Ze; Weng, Yan‐Mei; Geng, Chang‐An; Chen, Ji‐Jun (Chinese journal of chemistry, 2024)
Comprehensive Summary Eight new guaiane‐type sesquiterpenoid trimers, artemsieverolactones A—H, possessing unprecedented scaffolds via biocatalyzed [4+2] Diels−Alder cycloaddition reactions were identified from Artemisia sieversiana. Their structures were determined by comprehensive spectroscopic data, single‐crystal X‐ray diffraction analyses, and ECD calculations. In terms of structure, artemsieverolactones A—H are first examples of sesquiterpenoid trimers from guaiane‐type sesquiterpenoid through four different [4+2] Diels−Alder cycloaddition models. Antihepatic fibrosis assay suggested that five compounds exhibited activity against HSC‐LX2 with IC50 values ranging from 37.8 to 117.1 μmol/L. The most active artemsieverolactone B (2) displayed significant inhibitory activity against HSC‐LX2 with IC50 value of 37.8 μmol/L, which was 3 times more active than the positive drug silybin (IC50, 139.7 μmol/L). Preliminary mechanism study revealed that artemsieverolactone B could inhibit the deposition of human collagen type I (Col I), human hyaluronic acid (HA), and human laminin (HL) with IC50 values of 40.4 μmol/L (Col I), 55.1 μmol/L (HL), 47.3 μmol/L (HA), which was 2 to 3‐fold more potent than silybin. Bioassay‐guided investigation led to the discovery of eight novel guaiane‐type sesquiterpenoid trimers, artemsieverolactones A—H, which can be classified into four different types based on the connecting models of three guaianolide units. Most of the compounds showed inhibitory activity on HSC‐LX2 cells. Artemsieverolactone B (2) exhibited significant inhibition on HSC‐LX2 with an IC50 value of 37.8 μmol/L, and inhibited the deposition of human collagen type I (Col I), human hyaluronicacid (HA) and human laminin (HL) with IC50 values of 40.4, 47.3 and 55.1 μmol/L, respectively.